Deciphering the Behavioral Response of Meloidogyne incognita and Fusarium oxysporum Toward Mustard Essential Oil - Dutta, Anirban; Mandal, Abhishek; Kundu, Aditi; Malik, Monika; Chaudhary, Amrendra; Khan, Matiyar Rahaman; Shanmugam, Veerubommu; Rao, Uma; Saha, Supradip; Patanjali, Neeraj; Kumar, Rajesh; Kumar, Anil; et al. (Frontiers in Plant Science, 2021)
Environmental concerns related to synthetic pesticides and emphasis on adoption of integrated pest management concept as cardinal principle has strengthened the global research and development focus on botanical pesticides. Scientific understanding of the mode of action of biomolecules over a range of pests is key to successful development of biopesticides. The present investigation focuses on in silico protein-ligand interactions of allyl isothiocyanate (AITC), major constituent of black mustard (Brassica nigra) essential oil (MEO) against two pests Meloidogyne incognita (Mi) and Fusarium oxysporum f. sp. lycopersici (Fol), that cause severe yield losses in agricultural crops especially in vegetables. In vitro bioassay results of MEO against Mi exhibited exposure time dependent LC50 values of 47.7, 30.3, and 20.4 μg mL-1 at 24, 48 and 72 h of exposure, respectively. The study revealed short-term nematostatic activity at lower concentrations and nematicidal activity at higher concentrations upon prolonged exposure. MEO displayed excellent in vitro Fol mycelial growth inhibition, with EC50 value of 6.42 μg mL-1. In order to decipher the mechanism of action of MEO, its major component, allyl isothiocyanate (AITC; 87.6 %) identified by GC-MS was subjected to in silico docking and simulation studies against seven and eight putative target proteins of Mi and Fol, respectively. AITC exhibited highest binding affinity with the binding sites of acetyl cholinesterase (AChE), followed by odorant response gene-1 (ODR1), and neuropeptide G-protein coupled receptor (nGPCR) in Mi, suggesting possible suppression of neurotransmission and chemosensing functions. Among the target proteins of Fol, AITC was most effective in blocking chitin synthase (CS), followed by 2,3-dihydroxy benzoic acid decarboxylase (6m53), and trypsinase (1try), inferring these as the principal molecular targets of fungal growth. Taken together, the study establishes potential of MEO as a novel biopesticide lead, which will be utilized further to manage the Mi-Fol disease complex.